2017
DOI: 10.3390/s17030447
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Citrus Soil Moisture and Nutrients Using an IoT Based System

Abstract: Chongqing mountain citrus orchard is one of the main origins of Chinese citrus. Its planting terrain is complex and soil parent material is diverse. Currently, the citrus fertilization, irrigation and other management processes still have great blindness. They usually use the same pattern and the same formula rather than considering the orchard terrain features, soil differences, species characteristics and the state of tree growth. With the help of the ZigBee technology, artificial intelligence and decision s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(76 citation statements)
references
References 15 publications
0
76
0
Order By: Relevance
“…With the help of IEEE 802.15.4, which is a suite of high-level communication technology, artificial intelligence, and decision support technology, the authors of [19] have developed research on the agricultural application of IoT technology to monitor real-time moisture and nutrients of citrus, along with an analysis of the combination of fertilizer support systems and irrigation. However, this research has weaknesses, which include system complexity and high costs.…”
Section: Smart Agriculture and Related Workmentioning
confidence: 99%
“…With the help of IEEE 802.15.4, which is a suite of high-level communication technology, artificial intelligence, and decision support technology, the authors of [19] have developed research on the agricultural application of IoT technology to monitor real-time moisture and nutrients of citrus, along with an analysis of the combination of fertilizer support systems and irrigation. However, this research has weaknesses, which include system complexity and high costs.…”
Section: Smart Agriculture and Related Workmentioning
confidence: 99%
“…Soil characteristics could be particularly strong predictors of species diversity and composition in harsh environmental conditions, poorly developed soils [27], and in heterogeneous environments where the spatial distribution of plant species depends on a specific niche [43]. For example, the diversity and distribution of plant species are associated with soil available nitrogen and phosphorus [44], soil moisture and nutrients [45,46], as well as soil chemistry (soil pH, calcium, and organic carbon) [47,48]. An earlier study revealed a strong linkage between plant communities and soil microbial communities in the Tumen River Basin [14], and although not investigated here it is possible that soil microbial composition varies with altitude.…”
Section: Discussionmentioning
confidence: 99%
“…Wireless sensor node is used to predict fertilization and irrigation management. Result showed the increase of production of citrus [1]. Proposed a method only for monitoring crop with IoT, but as a future enhancement for automated irrigation and to secure the land using camera surveillance.…”
Section: Related Workmentioning
confidence: 99%